Logics of accountability: Cross-national patterns in school-level controls - Taeyeon Kim; John T. Yun (Education Policy Analysis Archives, 2019)
This paper explores multiple logics of accountability by examining patterns of control of various school functions under different accountability systems. Research has shown that accountability is a global phenomenon, but how accountability is understood and enacted is locally contextualized, which implies the existence of multiple logics of accountability in practice. By linking theoretical arguments rooted in literature to empirical evidence observed in TALIS 2013, we aim to theorize logics of accountability and then demonstrate the existence of those logics across countries. We first developed a framework of logics of accountability: control-based, professional-based, test-based, and process-based accountability. We then empirically analyzed three types of control—external, internal, and mixed control—at the school level across countries and within four content areas—assessment, human resource, curriculum, and budget—to infer how each country consistently follows a logic of accountability in their schooling practices. We found that a few countries followed a relatively pure form of control-based, professional-based, and process-based logic; however, most countries followed mixed-forms of logic. Our findings provide a systematic approach for the mapping of accountability logics across countries and suggest that more thought should be paid to how the underlying logic of accountability should manifest across these different functions.